Application of The Discovery Method in Improving Learning Outcomes in Recognizing The Shapes of Objects at Mi Ma’arif Nu 01 Pandansari - Khasanah, Uswatun; Hasanah, Uswatun; Ariani, Uti; Rachmah, Uun Fitriana (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to apply the discovery learning method to improve learning outcomes in recognizing object shapes in grade 2 students of MI Ma'arif NU 01 Pandansari. The discovery learning method was chosen because it can increase students' active involvement in the learning process through their own discovery. This study uses a classroom action research (CAR) approach with the research subjects being grade 2 students consisting of 25 students. The research procedures include planning, implementation, observation, and reflection. Learning using the discovery learning method is carried out through a series of activities that involve students in exploring object shapes directly, such as through games or observation activities. The results of the study showed an increase in student learning outcomes after the application of the discovery learning method. Before this method was applied, students had a limited understanding of object shapes, but after learning, students' understanding increased significantly, as evidenced by better test results and students' ability to recognize various object shapes. Thus, it can be concluded that the discovery learning method is effective in improving learning outcomes in recognizing object shapes in grade 2 students of MI Ma'arif NU 01 Pandansari.